التموقع التسويقي كخيار إستراتيجي لنجاح الإستراتيجية التسويقية -دراسة حالة مؤسسة جازي- - بـــــاني, فتحي; محمودي, أحمد (جامعة الوادي - University of Eloued, 2020)
التموقع التسويقي هو إستراتيجية تسويقية تهدف إلى تمييز المؤسسة ومنتجاتها عن المنافسين، حيث تخصص المؤسسات إستثمارات كبيرة لبناء صورة ذهنية قوية لها في أذهان المستهلكين، مما يمكنها من مواجهة المحيط التنافسي المتغير بشكل مستمر. من الواضح أن هذه العملية ليست بالمهمة السهلة لأنها تتطلب فهما عميقا للأسواق، المنافسة والموارد، وبما أن هذه العملية عي ذات صلة وثيقة بالاسواق المستهدفة وفئات المستهلكين، وباعتبار أنها خطوة جوهرية في إعداد الإستراتيجية التسويقية، فإن نجاح المؤسسة في تشكيل صورة ذهنية ناصعة لمنتجاتها أو التموقع الجيد في أذهان المستهلكين، هذا حتما سيؤدي إلى نجاح الإستراتيجية التسويقية للمؤسسة. تعتبر جازي "أوبتيموم تيليكوم" من اهم المؤسسات المتواجدة في مجال الإتصالات، لذلك تم دراستها كحالة لمعرفة فعالية تحسين صورتها للتأثير على إدراك المستهلكين الحاليين والمحتملين وبالتالي التأثير على سلوكهم الشرائي Marketing positioning is a marketing strategy that aims to distinguish the institution and its products from competitors, where institutions allocate large investments to build a strong mental image in the minds of consumers, which enables them to face the constantly changing competitive environment. It is clear that this process is not an easy task because it requires a deep understanding of the markets, competition and enterprise resources, and since this process is closely related to the targeted markets and consumer groups, and as it is an essential step in preparing the marketing strategy, the organization’s success in forming a clear mental image of its products or Good positioning in the minds of consumers, this will inevitably lead to the success of the enterprise's marketing strategy. Djezzy "Optimum Telecom" is one of the most important institutions in the field of telecommunications, so it was relied upon as a study case to know the effectiveness of improving its image to affect the awareness of current and potential consumers and thus influence their purchasing behavior.
Marketing positioning as a strategic choice for the success of the marketing strategy - Djezzy Institution Case Study
مقال
Keywords: التموقع التسويقي، الإستراتيجية التسويقية، الصورة الذهنية، التميز; Marketing positioning, Marketing strategy, Mental image, Excellence